Female Genital Cutting, Women's Health, and Development : The Role of the World Bank - Rogo, Khama; Subayi, Tshiya; Toubia, Nahid; Sharief, Eiman Hussein (Washington, DC : World Bank, 2012)
Female Genital Mutilation or Cutting (FGM/C) is a customary practice indigenous to 28 African countries and is also reported among African immigrants in countries in Europe, North America, Australia, and New Zealand. FGM/C is also found in some Muslim communities in the highlands of India. The report documents the extent to which FGM/C is perceived as a public health issue. The social and political situation in Somalia in light of the civil unrest is likely to be a challenge in expanding the reach and effectiveness of FGC interventions particularly in rural communities. The experience of Kouroussa in Haute Guinea through the Population and Reproductive Health Project presented at the development marketplace 2000 competition with the project ending female genital cutting also gave the opportunity to the Bank to address FGM/C in a more systematic way, using all available resources. Other opportunities for supporting FGM/C programs include classic World Bank lending instruments such as Sector Investment Loans (SIL), Learning and Innovative Loans (LILs), Sector Wide Approaches (SWAPs), and poverty reduction strategies. These operations can address the issue of FGM from broader women's health and economic development angle. This position paper defines the scope of the problem in the region, suggests options for interventions, reviews constraints and identifies areas of interaction for the Bank. It also gives options for future actions within the different sectors of the World Bank Group.